DEVELOPING STUDENTS' SKILLS TO CRITICALLY ANALYZE LITERARY CHARACTERS - Akabirova Mehriniso Baxtiyorovna (Modern American Journals, 2025)
The article reveals the peculiarities of development of students' critical thinking in the process of studying works of art, gives definitions of the concept of "critical thinking" put forward by famous psychologists, characterizes the system of work on the analysis of the work, in the process of which students develop the ability to critically evaluate literary heroes.
Keywords: critical thinking, critical assessment, awareness, conviction, independent conclusions, arguments, discussion, point of view, analysis